2023
DOI: 10.1021/acs.accounts.2c00827
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Near-Infrared Luminescence of Self-Assembled Platinum(II) Complexes: From Fundamentals to Applications

Abstract: Conspectus Designing bright and efficient near-infrared (NIR) emitters has drawn much attention due to numerous applications ranging from biological imaging, medical therapy, optical communication, and night-vision devices. However, polyatomic organic and organometallic molecules with energy gaps close to the deep red and NIR regime are subject to dominant nonradiative internal conversion (IC) processes, which drastically reduces the emission intensity and exciton diffusion length of organic materials and henc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…While closely related iridium­(III) complexes may be superior in many respects, Pt­(II) systems do offer some rather unique features. These d 8 complexes are typically square-planar, and face-to-face interactions between them may lead to the formation of aggregates or excimers whose excited states are stabilized relative to those of the isolated molecules . The resulting red-shifted emission offers an interesting potential strategy for achieving more efficient red or near-infrared emitters .…”
Section: Introductionmentioning
confidence: 99%
“…While closely related iridium­(III) complexes may be superior in many respects, Pt­(II) systems do offer some rather unique features. These d 8 complexes are typically square-planar, and face-to-face interactions between them may lead to the formation of aggregates or excimers whose excited states are stabilized relative to those of the isolated molecules . The resulting red-shifted emission offers an interesting potential strategy for achieving more efficient red or near-infrared emitters .…”
Section: Introductionmentioning
confidence: 99%
“…To obtain highly efficient Pt-based OLEDs, Pt-Pt interactions have been proven to be an effective strategy. [18][19][20] In addition, deplanarization of planar Pt complexes may be an effective way to solve the concentration quenching problem caused by severe π-π stacking, 21,22 thereby enabling Pt complexes to exhibit better external quantum efficiency (EQE) and alleviate efficiency roll-off.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in NIR OLED emitters have progressed remarkably through the use of metal complexes such as Pt­(II), Ir­(III), and Os­(II) to achieve efficient and longer-wavelength emissions that even extend into the NIR­(II) window. Furthermore, prior studies have demonstrated the construction of flexible oximeters by establishing NIR OLED arrays on a polyethylene naphthalate (PEN) substrate, thereby providing the potential of NIR OLEDs in bioelectronic applications. , However, despite persistent efforts in research and development, the practical application of NIR OLEDs to wearable devices remains a challenge because of their limited flexibility, which is caused by the brittle indium tin oxide (ITO) electrode used for NIR OLED fabrication.…”
Section: Introductionmentioning
confidence: 99%